DEVELOPMENT OF THE STRUCTURAL MODEL OF THE INERTIAL MEASUREMENT MODULE - Kirichuk, Yury; Nazarenko, Natalia; Mospan, Anton (SWorld-Ger Conference proceedings, 2023)
The work deals with the development of the structural model of the inertial measuring module and the selection of its constituent elements